Biodegradable chitosan-based composites with dual functions acting as the bone scaffold and the inflammation inhibitor in the treatment of bone defects. Issue 12 (13th August 2018) - Ren, Xin; Chen, Chen; Hou, Yi; Huang, Min; Li, Yubao; Wang, Danqing; Zhang, Li
ABSTRACT: A composite based on nano-hydroxyapatite (n-HA)/chitosan (CS) and loaded with ciprofloxacin (CIP) was prepared and its physicochemical properties, antibacterial properties, drug release ability, and bone regeneration ability were characterized. The physicochemical results indicated that the n-HA/CS composite exhibited about a 70/30 ratio of n-HA to CS, and the size of n-HA in the n-HA/CS composite was about 100 nm. According to the results of the antibacterial test, the materials loaded with CIP presented excellent antibacterial activity. In addition, the in vivo concentration of CIP far surpassed the minimum inhibitory concentration (0.25–2 µg mL −1 ). In vitro standard deviation-rats marrow mesenchymal stem cells (MSCs) tests, including cell counting kit-8 assay and scanning electron microscopy images of MSCs, revealed that both of the scaffolds could support MSCs proliferation and attachment. The in vivo results indicated that n-HA/CS-CIP could promote the formation of bone tissues and blood vessels, and displayed a better repair ability for bone defect than the control group of n-HA-CIP. The CS-based composite with dual functions has a good perspective which would justify further research. GRAPHICAL ABSTRACT: